Le contrôle social dans la société canadienne du Régime français au XVIIIe siècle - Lachance, André (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
The article examines certains aspects of the social control in Canadian society during the French régime in the xvmth century. Based on the finding that the number of cases that went before the king's court for certain types of crime was relatively small, the author concludes that social control was exercised more by the society itself than by its institutions. The justice apparatus had little control over the Canadian people as a whole, due to its lack of sufficient peace officers, the tremendous size of the country and its meagre and scattered population. It was the elite, as models anddefiners of the norms, and the family, as the principal instrument in the regulation of conduct, that played an important role in the social control of Canadian society. It was this system that enabled XViUth century Canada to maintain a very low rate of what we considered serious crimes.